Measuring the Metallicity of Early-type Galaxies - Wu, Yu-Zhong (Astrophysical journal. Letters, 2020)
We use data for 6048 early-type galaxies (ETGs) from Galaxy Zoo 1 that have been cross-matched with the catalog of the MPA-JHU emission-line measurements for the Sloan Digital Sky Survey Data Release 7. We measure the metallicity of these ETGs by excluding various ionization sources, and study other properties as well. We use the optimal division line of W2-W3 = 2.5 as a diagnostic tool, and for the first time derive metallicity measurements for 2218 ETGs. We find that these ETGs actually are closer to H ii regions as defined by Kauffmann et al. in the Baldwin-Philips-Terevich diagram, and they display younger stellar populations. We present a full mass-metallicity relation and find that most ETGs have lower metallicities than star-forming galaxies (SFGs) at a given galaxy stellar mass. We use five metallicity calibrators to check our results. We find that these metallicity indicators (R23, O32, and O3S2) give consistent results. We suggest that the remaining two metallicity calibrators, which increase metallicity by N-enrichment, can be used to calibrate metallicities for SFGs, but not to estimate the metallicities of ETGs.